Implementasi Algoritma Rabin-Karp pada Pendeteksian Plagiarisme - Ari Kurniawan Saputra; Robby Yuli Endra; Fenty Ariani; Tia Tanjung; Agustan Prakarsya (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2023)
Implementation of Rabin-Karp Algorithm in Plagiarism Detection - Plagiarism is a crime and a scourge of science. To avoid plagiarism in scientific articles, as in the case of this research, string-matching methods can be used. This study aims to implement the Rabin-Karp Algorithm in detecting plagiarism in scientific writing based on the level of text similarity. The Rabin-Karp algorithm was chosen for this research problem because previous studies revealed that the Rabin-Karp premise is to separate the hash value of the input string from the text substring. Assuming they are the same, the character check is performed one more time, and if not, moves the substring aside. The main part of this computation exhibit is successfully calculating the hash of the substring when applied. This research is quantitative. The stages of this research flow were carried out by testing the implementation of the Rabin-Karp algorithm. Based on the calculation above, the percentage of similarity between Test Sentence 1 and Test Sentence 2 is 77.96%. Referring to previous studies, the Winnowing algorithm was found to be better at detecting text similarities than the Rabin-Karp algorithm. This is shown in the results of the similarity detection test of 30 paper documents as test data with the results of the average percentage value. Rabin-Karp Algorithm 41.41% and Winnowing Algorithm 35.15%. This study shows that the Rabin-Karp Algorithm does not work optimally in detecting text similarity, so further research needs additional methods to calculate a good level of similarity to optimize the performance of the Rabin-Karp Algorithm.